2019
DOI: 10.1007/s00216-019-01939-3
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous analysis of natural pigments and E-141i in olive oils by liquid chromatography–tandem mass spectrometry

Abstract: This work describes the development of an ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method for the determination of carotenoids (ß-carotene, lutein, ß-criptoxanthin, neoxanthin, violaxanthin) and chlorophylls, as well as their related compounds (chlorophyll A and B, pheophytin A and B and the banned dyes Cu-pyropheophytin A, Cu-pheophytin A and B) in olive oils. For this purpose, the feasibility of electrospray (ESI), atmospheric pressure chemical ionization (APCI) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The artificial neural networks applied to visible spectroscopic data could be used to determine varietal quantifications based on the pigment profile of monovarietal extra virgin olive oils at 10% and 2.8% for the linear and non-linear models, respectively Aroca-Santosa, Cancilla, Pérez-Pérez, Moral, and Torrecilla (2016) Detection of possible fraud markers Ultra-high-performance liquid chromatography tandem mass spectrometry coupled with two types of atmospheric pressure ionizations (chemical and photoionization) were found efficient in determining natural color pigments (carotenoids, chlorophylls and chlorophyll derivatives) as well as artificial ones (E141i) in olive oils. These methods were applicable in pigment profile identification as well as the detection of possible exogenous adulterants Arrizabalaga-Larrañaga, Rodríguez, Medina, Santos, and Moyano (2019) Cultivar differentiation Five different Greek olive oil cultivars were successfully characterized and classified based on acidity, total chlorophylls and carotenoids, myristic, margaric, stearic, arachidic, and eicosenoic acids at a rate of 91.9% and 81.1% by using original and cross-validation methods, respectively Karabagias et al (2019) Geographical differentiation Geographical discrimination power of several chemical parameters (total phenol content, fatty acid and phenol profile, total carotene and chlorophyll content and oxidative stability) and mid-infrared spectroscopy on olive oils was investigated. It was found that combination of chemical parameters was better than mid-IR spectroscopy in classification of monovarietal olive oil obtained from geographically close regions of Turkey Uncu and Ozen (2016) Cultivar discrimination Monovarietal extra virgin olive oils could be classified up to 94.4% according to their variety by using Raman spectroscopy highly correlated with both carotenoid and fatty acid composition of olive oils.…”
Section: Aim Main Findings Referencementioning
confidence: 99%
“…The artificial neural networks applied to visible spectroscopic data could be used to determine varietal quantifications based on the pigment profile of monovarietal extra virgin olive oils at 10% and 2.8% for the linear and non-linear models, respectively Aroca-Santosa, Cancilla, Pérez-Pérez, Moral, and Torrecilla (2016) Detection of possible fraud markers Ultra-high-performance liquid chromatography tandem mass spectrometry coupled with two types of atmospheric pressure ionizations (chemical and photoionization) were found efficient in determining natural color pigments (carotenoids, chlorophylls and chlorophyll derivatives) as well as artificial ones (E141i) in olive oils. These methods were applicable in pigment profile identification as well as the detection of possible exogenous adulterants Arrizabalaga-Larrañaga, Rodríguez, Medina, Santos, and Moyano (2019) Cultivar differentiation Five different Greek olive oil cultivars were successfully characterized and classified based on acidity, total chlorophylls and carotenoids, myristic, margaric, stearic, arachidic, and eicosenoic acids at a rate of 91.9% and 81.1% by using original and cross-validation methods, respectively Karabagias et al (2019) Geographical differentiation Geographical discrimination power of several chemical parameters (total phenol content, fatty acid and phenol profile, total carotene and chlorophyll content and oxidative stability) and mid-infrared spectroscopy on olive oils was investigated. It was found that combination of chemical parameters was better than mid-IR spectroscopy in classification of monovarietal olive oil obtained from geographically close regions of Turkey Uncu and Ozen (2016) Cultivar discrimination Monovarietal extra virgin olive oils could be classified up to 94.4% according to their variety by using Raman spectroscopy highly correlated with both carotenoid and fatty acid composition of olive oils.…”
Section: Aim Main Findings Referencementioning
confidence: 99%
“…The chromatographic separation of all target compounds was performed in a reversed-phase UHPLC Accucore C18 column, under a quaternary gradient elution with water, methanol, acetonitrile, and acetone as the mobile phase components. The gradient elution was based on a chromatographic method previously developed for the separation of chlorophylls and carotenoids (Arrizabalaga-Larrañaga, Rodríguez, Medina, Santos, & Moyano, 2019). However, some modifications were required to deal with the simultaneous determination of capsaicinoids and carotenoids.…”
Section: Uhplc-hrms Methods Developmentmentioning
confidence: 99%
“…As a consequence of the isotope profile of copper, the isotopic distribution of copper chlorophyll derivatives ( Figure 2) shows an isotopic pattern that resembles the significant abundance of Cu 64.9272 (44.6%) to the isotope pattern of copper. As an example, Figure 2A displays the isotopic pattern of copper pyropheophytin a (C 53 H 70 CuN 4 O 3 ), the main chlorophyll derivative in lipophilic green food colorants (E-141i) (Roca et al, 2010;Fang et al, 2015;Arrizabalaga-Larrañaga, Rodríguez, Medina, Santos, & Moyano, 2019), which was calculated with the Compass Isotope Pattern software (section 2.3). For this copper chlorophyll compound, the abundance of the third isotope is higher (0.62747) than the second one (0.59716), as can be confirmed in Figure 3A with the authentic standard of copper pyropheophytin a.…”
Section: Theoretical Principlementioning
confidence: 99%